Intra-mesenteric steroids for steroid-refractory graft-versus-host disease in pediatric patients: A safe option - Ana M. Aristizábal; Lina P. Montaña; Jaiber Gutiérrez; Diego Medina; Alexis A. Franco; Eliana Manzi; Ángela Devia Zapata; Walter Mosquera (Biomédica: revista del Instituto Nacional de Salud)
Introduction. Graft-versus-host disease is a serious complication after hematopoietic stem cell transplantation and is a major cause of death post-transplantation. Approximately 50% of acute graft-versus-host disease patients do not respond to systemic steroids and their prognosis is poor regardless of the treatment. This study describes our experience with pediatric patients diagnosed with steroid-refractory graft-versus-host disease who received intra-mesenteric steroid treatment. Objective. To determine the outcomes of intra-mesenteric steroid use in the management of pediatric patients diagnosed with refractory graft-versus-host disease. Materials and methods. The study included patients under 18 years old with allogeneic hematopoietic stem cell transplantation who underwent intra-mesenteric steroid injection for resistant gastrointestinal graft-versus-host disease between January, 2016, and December, 2021. Methylprednisolone was administered via intra-arterial injection through the celiac trunk and the superior and inferior mesenteric arteries. Results. We collected data on 21 patients: nine (90%) responded with a subjective decrease in fecal output and a reduction in bilirubin and transaminases. Seven patients required a second intra-mesenteric injection and presented a complete response in 85% of the cases. Only one patient experienced local complications after the procedure. Twelve patients (57%) died with one death due to acute graft-versus-host disease. Conclusion. Reports in the adult population have shown an approximately 50% response rate with few complications, making it a second-line management standard. As far as we know, this is the largest pediatric cohort reported in Latin America. Our findings suggest that intra-mesenteric steroid administration for managing hepatic and gastrointestinal graftversus-host disease may be considered an early adjuvant treatment in patients with steroidrefractory graft-versus-host disease.